PROCEDURAL INDEPENDENCE INVESTIGATOR: IDENTIFICATION ISSUES CATEGORICAL AFFILIATION - Khvedelidze, Теймураз Бичикоевич; Sailibayeva, Жанель Юрсуновна; Toleubekova, Бахитжан Хасеновна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2024)
Issues related to the determination of the place and role of the procedural independence of the investigator do not lose their relevance since its legislative establishment. The most frequently considered subjects of dispute between theorists and practitioners are the problems of legal guarantee of the procedural independence of the investigator. It seems to us that these problems should be resolved on the basis of determining the categorical affiliation of the most controversial concept.